Early hydration process of the cement–lime system. Issue 4 (1st September 2018) - Zhang, Hui; Su, Yufeng; Yang, Zhenghong; Zhang, Xiong
Abstract: Autoclaved aerated concrete is a widely used wall material, of which the cementitious materials are cement and lime. In this study, hydration process of the cement–lime system and the influence of initial temperature, water to lime and cement ratio (W/LC), and lime to cement ratio (L/C) on the cement–lime system heat release process were investigated during the first 2 h of hydration. The results indicate that the hydration process of the cement–lime system can be divided into three stages – initial stage, middle stage, and final stage. A prolonged hydration time can be observed with a lower initial temperature, higher W/LC, and lower L/C. The hydration time doubles for every 10°C reduction in initial temperature. A lower W/LC moves the induction and acceleration periods forward but decreases hydration rates if without the effect of the heat released. There might be a critical point of CaO dosage in the cement–CaO system that can change the hydration mechanism. The investigations uncover regulations and effect factors of the hydration process of the cement–lime system which can help to improve the quantity of autoclaved aerated concrete.